Pemanfaatan Rapor Pendidikan dalam Upaya Kepala Sekolah Meningkatkan Kualitas Pembelajaran melalui Refleksi dan Perbaikan Pembelajaran oleh Guru di Sekolah Dasar - Asmaudin, Anif; Fajrie, Nur; Fathurohman, Irfai (Journal Prakarsa Paedagogia, 2024)
This study examines the utilization of the Education Report (Rapor Pendidikan) as a tool for school principals to improve the quality of learning through reflection and improvement by teachers in elementary schools. A descriptive quantitative approach was used, with data collected through questionnaires distributed to principals and teachers at each elementary school in Jepara District. The results show that the Education Report has been utilized for data-based planning, formulating school policies/programs, teacher learning activities aimed at enhancing teaching knowledge and skills, and for reflection and improvement of learning. Overall, the platform has proven beneficial in improving the quality of learning in elementary schools in Jepara District. Recommendations include: more extensive socialization about the benefits and usage of the platform, intensive training for principals and teachers on data analysis and decision-making, and the development of the platform with more complete and user-friendly features.